2006
DOI: 10.1542/peds.2005-3140
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four-Hour Esophageal Impedance-pH Monitoring in Healthy Preterm Neonates: Rate and Characteristics of Acid, Weakly Acidic, and Weakly Alkaline Gastroesophageal Reflux

Abstract: We present the first study using 24-hour impedance-pH recordings in asymptomatic premature neonates. Previous studies that used pH-metry suggested that neonatal cardiorespiratory symptoms could be related to acid gastroesophageal reflux. However, pH-metry could not detect accurately weakly acidic or nonacid reflux. Our healthy premature neonates had approximately 70 reflux events in 24 hours, 25% of which were acid, 73% were weakly acidic, and 2% were weakly alkaline. The number of reflux events per hour (2-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
158
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(186 citation statements)
references
References 25 publications
15
158
3
7
Order By: Relevance
“…Previous results have shown that acid refluxes are present in infants, even in newborns, and suggest they are responsible for pathological consequences, including laryngitis (Cresi et al, 2013;Jadcherla et al, 2011;López-Alonso et al, 2006;Shin et al, 2012;Vermeylen et al, 2005). However, our results may not apply to reflux laryngitis secondary to weakly acid reflux, which are especially prominent in newborns.…”
Section: Reflux Laryngitis Modelcontrasting
confidence: 58%
“…Previous results have shown that acid refluxes are present in infants, even in newborns, and suggest they are responsible for pathological consequences, including laryngitis (Cresi et al, 2013;Jadcherla et al, 2011;López-Alonso et al, 2006;Shin et al, 2012;Vermeylen et al, 2005). However, our results may not apply to reflux laryngitis secondary to weakly acid reflux, which are especially prominent in newborns.…”
Section: Reflux Laryngitis Modelcontrasting
confidence: 58%
“…(8) MII/pH allows us not only to evidence esophageal acid exposure, but also to detect non-acid or weakly acidic reflux events that are prevalent in newborns. (9) It was demonstrated that this technique is able to recognize a higher number of refluxes than traditional pH-metry (10) and it is particularly suitable in newborns, (11) and its application in term and preterm newborns with GERD symptoms has been shown to be safe and well tolerated. (12) MII/pH allows for the observation of some distinctive features of reflux events in these patients, which could influence the corresponding clinical approach.…”
Section: Introductionmentioning
confidence: 99%
“…GERD is considered common in premature infants younger than 34 weeks gestational age, but the severity of GERD is not significantly different in symptomatic and asymptomatic infants [37,40,50]. Some authors stated that GERD is common even in premature infants younger than 32 weeks gestational age [33,34,36,41,44].…”
Section: The Age Of the Premature Child When The Pattern Of Gerd Can mentioning
confidence: 99%
“…Other studies argue that a greater number of reflux episodes per hour occur during mealtime, compared to the fasting period [50]. One study showed that reflux episodes are most common between 120 and 150 minutes after a meal [33].…”
Section: Symptom Variation During the Course Of The Daymentioning
confidence: 99%